ATIVIDADES DESENVOLVIDAS PELO CENTRO DE ESTUDOS E PESQUISAS DE ÁGUAS SUBTERRÂNEAS ARARAQUARA - SP - Mendonça, José Luiz Galvão de; Loffredo, Luiz Fernando (Águas Subterrâneas, 1988)
Resumo não disponível.